PENGARUH ECONOMIC VALUE ADDED DAN FAKTOR LAINNYA TERHADAP HARGA PASAR SAHAM - Julianti Sjarief; Aruna Wirjolukito (Media Riset Akuntansi, Auditing & Informasi, 2004)
In financial management perspective, the objective of the firm is maximizing firm value that reflects wealth of the owners. Firm value, so far is acknowledge as a fine parameter in measuring management performance. Acco4ding to many literature we know before, good perfonnance will absolutely increase value of stockholders'equity After ROl become famous parameter, nowadays managers look around for better measurement. EVA so far, become one of them and in many cases proved that objectives. This paperexamine EVA, a new comer benchmark and tool, as measure-ment of management performance that puled by stock price. In regression method used, we simply find that EVA has advantage. Result from this study found that EVA does better status rather than leverage ratio and ages, that reflect firms' reputation before public.Keywords: EVA, DER, umurperusahaan, harga saham